Kv1.3 Channel Blockade Modulates the Effector Function of B Cells in Granulomatosis with Polyangiitis - Land, Judith; Lintermans, Lucas L.; Stegeman, Coen A.; Muñoz-Elías, Ernesto J.; Tarcha, Eric J.; Iadonato, Shawn P.; Heeringa, Peter; Rutgers, Abraham; Abdulahad, Wayel H. (Frontiers in Immunology, 2017)
B cells are central to the pathogenesis of GPA, exhibiting both (auto)antibody dependent and independent properties. Class-switched memory B cells in particular are a major source of pathogenic autoantibodies. These cells are characterized by high expression levels of Kv1.3 potassium channels which may offer therapeutic potential for Kv1.3 blockade. In this study, we investigated the effect of the highly potent Kv1.3 blocker ShK-186 on B cell properties in GPA in vitro. Circulating B cell subsets were determined from 33 GPA patients and 17 healthy controls (HC). Peripheral blood mononuclear cells (PBMC) from GPA patients and HC were stimulated in vitro in the presence and absence of ShK-186. The production of total and PR3-ANCA IgG was analyzed by ELISA and Phadia EliA, respectively. In addition, effects of ShK-186 on B cell proliferation and cytokine production were determined by flow cytometry. The frequency of circulating switched and unswitched memory B cells was decreased in GPA patients as compared to HC. ShK-186 suppressed the production of both total and PR3-ANCA IgG in stimulated PBMCs. A strong decrease in production of TNFα, IL-2 and IFNγ was observed upon ShK-186 treatment, while effects on IL-10 production were less pronounced. As such, ShK-186 modulated the TNFα/IL-10 ratio among B cells, resulting in a relative increase in the regulatory B cell pool. ShK-186 modulates the effector functions of B cells in vitro, by decreasing autoantibody and pro-inflammatory cytokine production. Kv1.3 channel blockade may hold promise as a novel therapeutic strategy in GPA and other B cell mediated autoimmune disorders.